2020
DOI: 10.1186/s42483-020-00059-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci for disease resistance to false smut of rice

Abstract: False smut of rice, an important emerging disease caused by Ustilaginoidea virens, greatly reduces grain yield and deteriorates grain quality in many rice-growing regions worldwide. Identification of quantitative trait loci (QTL) conferring false smut resistance will facilitate incorporation of false smut resistance into elite cultivars. In this study, a set of recombinant inbred lines (RILs) derived from a cross of a resistant rice landrace MR183-2 and a high susceptible line 08R2394 were evaluated to map res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…; Li et al 2011; Andargie et al 2018,Han et al 2020) whereas the QTLs on chromosome 7 and 9 were detected for the rst time in this report. Zhou et al 4% phenotypic variance.…”
supporting
confidence: 47%
See 2 more Smart Citations
“…; Li et al 2011; Andargie et al 2018,Han et al 2020) whereas the QTLs on chromosome 7 and 9 were detected for the rst time in this report. Zhou et al 4% phenotypic variance.…”
supporting
confidence: 47%
“…Recently, ve QTLs associated with RFS resistance were mapped on chromosomes 2, 4, 8 and 11 using a RIL population derived from a cross between RFS resistant rice cultivar MR183-2 and highly susceptible rice cultivar 08R2394. Among these, qFSr8-1 accounted larger phenotypic variance (Han et al 2020). Recent progress also suggested that resistance genes (R genes) are responsible for conferring resistance to false smut (Han et al 2020;Qiu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of author's knowledge, only two reports published that showed the identi cation of disease resistance genes (R genes) against RFS in rice (Han et al 2020, Qiu et al 2020. In this study, we also have reported identi cation of putative disease resistance genes conferring resistance to rice false smut.…”
Section: Disease Resistance Genes Control the Rfs Resistance In Ricementioning
confidence: 66%
“…Host resistance is the most effective and environmentally friendly method to cope with the designated diseases of rice [10]. Considering the economic feasibility, rice diseases have been extensively studied in [11][12][13]. So, the study on the resistance ability of Uttar Lakshmi towards disease and insect pests was important during the release of the variety for extensive cultivation.…”
Section: Reaction To Biotic and Abiotic Stressesmentioning
confidence: 99%